Beyond the school gates : questioning the extended schools and full service agendas - Cummings, Colleen; Dyson, Alan.; Todd, Liz. (Milton Park, Abingdon, Oxon : New York : Routledge, 2011)
This book is essential reading for anyone interested in the role of full service and extended schools - those offering new services to students, families and communities beyond regular school hours.
Includes bibliographical references and index.
Keywords: Children with social disabilities -- Education -- Great Britain; Children with social disabilities -- Services for -- Great Britain; Community and school -- Great Britain